Future-Proofing Education: Developing Transdiscipllinary STEAM Models to Prepare Learners for a Workforce in the Forthcoming Era of Automation - Momi Bhattacharjya (Transdisciplinary journal of engineering & science, 2025)
This research examines the future of education, focusing on the need to adapt current transdisciplinary educational models to the demands of the automation-driven workforce. The study explores the shift from STEM to STEAM (Science, Technology, Engineering, Arts, and Mathematics), analyzing how the integration of the arts impacts student outcomes, attitudes, and creativity. It delves into the potential transformations in the job market and the vulnerabilities posed by automation in the 22nd century. Using an inductive approach, a systematic literature review was conducted, synthesizing insights from 75 relevant studies on transdisciplinary STEAM education. The research proposes innovative, transdisciplinary  STEAM  models aimed at cultivating resilience, innovation, and sustainable skillsets among students. The goal is to inform policymakers and educators on how to future-proof education, ensuring learners are equipped for the challenges and opportunities of an automated workforce.